(untitled) (Vietnam Journal of Community Medicine, 2026)
Background: Adolescent sexual and reproductive health (SRH) is essential for preventing unintended pregnancy and sexually transmitted infections. Objectives: To describe access to SRH information/services and KAP among adolescents aged 15–17 attending Hoc Mon District Health Center in 2025, and to analyze selected associated factors. Methods: A cross-sectional study was conducted among 218 adolescents selected by convenience sampling from 26 November 2024 to 11 March 2025. Data were collected using a structured questionnaire and analyzed using descriptive statistics, crude odds ratios, 95% confidence intervals and p<0.05. Results: Females accounted for 63.3% and 17-year-olds for 44.0%. The Internet was the most common information source (82.0%). Overall adequate knowledge, attitude and correct practice were 73.4%, 89.5% and 93.6%, respectively. Adequate knowledge of safe sex was 48.6%; adequate knowledge of fertile timing was 56.4%. Females were more likely to have adequate knowledge of fertile timing and adequate overall attitude. Ever having sexual intercourse was reported by 11.9%; consistent condom use among sexually active adolescents was 50.0%. Conclusions: KAP was generally favorable, but gaps remained in safe sex, fertile timing and consistent condom use. School-based, digital and adolescent-friendly counseling should be strengthened.